2014
DOI: 10.1557/opl.2014.957
|View full text |Cite
|
Sign up to set email alerts
|

Organic Semiconductor Thin Films Deposited by Resonant Infrared Matrix-Assisted Pulsed Laser Evaporation: A Fundamental Study of the Emulsion Target

Abstract: Poly (3-hexylthiophene) (P3HT) thin films were deposited using emulsion-based, resonant infrared matrix-assisted pulsed laser evaporation (RIR-MAPLE) from emulsions containing different solvents and different alcohols, to investigate the impact of emulsion on film morphology. The atomic force microscopy (AFM) and grazing-incidence, wide angle x-ray scattering (GIWAXS) results show that surface morphology of RIR-MAPLE as-deposited films can be varied from rough to smooth and the microcrystalline domain orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…14 Control of various process parameters has been shown to tune film morphology. For instance, MAPLE has been shown to control preferential crystal orientation and the extent of crystallinity in thin polymer films by adjusting the matrix formulation 17 and substrate temperature, 18 respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 Control of various process parameters has been shown to tune film morphology. For instance, MAPLE has been shown to control preferential crystal orientation and the extent of crystallinity in thin polymer films by adjusting the matrix formulation 17 and substrate temperature, 18 respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The development of matrix-assisted pulsed laser evaporation (MAPLE), which provides a gentle means for the deposition of high molecular polymers from the near-gas-phase growth conditions, offers a unique opportunity for bottom-up polymer film growth to control morphology. For instance, it has been shown that MAPLE can be used to control preferential crystal orientation and the extent of crystallinity in polymer thin films by adjusting the matrix formulation and substrate temperature, respectively. Recently, we demonstrated the sequential growth and crystallization of polymer thin films deposited via MAPLE at slow growth rates .…”
mentioning
confidence: 99%
“…Y. Liu (2014) analyzed the influence of the emulsion containing different organic solvents and various alcohols on the morphology properties of P3HT layers obtained using emulsion-based RIR-MAPLE (Er:YAG laser, λ = 2.9 µm) [144]. In the P3HT thin films deposition, a fluence of 1.46-1.6 J/cm 2 and targets prepared either from 0.5 wt.% P3HT in chlorobenzene, 1,2-dichlorobenzene, 1,2,4-trichlorobenzene, chloroform or trichloroethylene mixed with phenol and emulsified with water (1:0.5:4 ratio of emulsion components) or 0.5 wt.% P3HT in 1,2,4-trichlorobenzene mixed with phenol and emulsified with methanol, ethanol, 1-propanol or 1-butanol mixed with water (1:0.2:1:3 weight ratio of emulsion components) were used.…”
Section: Single Layers Based On Polymersmentioning
confidence: 99%
“…The vapor pressure of the solvents used as a matrix in the laser deposition is also an experimental parameter that can affect the surface properties of the deposited films. Thus, in the emulsion-based RIR-MAPLE, the low vapor pressure solvents, such as trichloroethylene or 1,2,4-trichlorobenzene, allow the deposition of films with a low roughness, preferentially with a vertical orientation of the microcrystalline domains, while the films obtained from high vapor pressure solvents are rough with a random orientation [144]. The films deposited using UV-MAPLE using low vapor pressure solvents show smoother surfaces compared to those prepared from high vapor pressure solvents [123].…”
Section: Conclusion and Challengesmentioning
confidence: 99%